The Excavation of Adab - Yang, Zhi
Mound I; Mound II; Mound III, the "Semitic Quarter״; Mound IV; Mound IVa. Stratigraphy of the Temple Mound; Mound VI; Mound IX; Mound XII; The City Wall. The Major Periods of Occupation at Adab.